Морфология преимагинальных фаз ольховой хохлатки - Долинская, И.В.; Ломакин, М.Д. (Вестник зоологии, 1983)
Premature stages and some ecological peculiarities of Nofodonta dromedarius L. of the Ukraine are described. The main diagnostic characters of the egg, caterpillar and chrysalis are outlined. Special attention is paid to characters that show stability under alcohol preservation.